Capsular Polysaccharide From Bacteroides fragilis Protects Against Ulcerative Colitis in an Undegraded Form - Zheng, Lijun; Luo, Meihua; Kuang, Gaobo; Liu, Yangyang; Liang, Debao; Huang, Haiqing; Yi, Xiaomin; Wang, Congfeng; Wang, Ye; Xie, Qiuling; Zhi, Fachao (Frontiers in Pharmacology, 2020)
The prominent human symbiont Bacteroides fragilis can protects animals from intestinal disease such as ulcerative colitis, and its capsular polysaccharide played a key role. We isolated B. fragilis strain ZY-312 from the feces of a healthy breasted infant and extracted its Zwitterionic Capsular Polysaccharides (ZPSs), named as TP2. In rats with 2,4-dinitrobenzenesulfonic acid (DNBS）induced enteritis, we found that TP2 at an optimal dose of 2.5 mg/kg could significantly alleviate enteritis, while reduced the degree of intestinal adhesions, the intestinal ulcer area and the incidence of ulcer in rats. In order to understand what exactly happens to TP2 after oral administration and the underlying mechanism of action, TP2 was labled with FITC and was orally administered in rats with the same pharmacodynamic dose of 2.5 mg/kg. It was found that TP2 was mainly distributed in the cecum and colorectum, but not detected in the blood and other organs except a compound with molecular weight more than that of TP2-FITC was found in liver tissue. During the absorption, distribution, metabolism, excretion of TP2 in body, TP2 was indigestible. These results were further confirmed by investigation in the simulated gastric, intestinal fluid, and colonic fluid with fecal microbiota in vitro, where TP2 kept unchanged at different time points. Furthermore, flora composition was analyzed in simulated colonic fluid with TP2 addition, it was found that TP2 increased the abundance of Faecalibacterium, Enterococcus romboutsia, Ruminococcaceae, and Bacteroides that are thought to increase the anti-inflammatory ability of the host, whereas the abundance of phylum Proteobacteria represented by Sutterella, Desulfovibrio, and Enterobacteriaceae was decreased. However, the amount of short-chain fatty acids (SCFAs) in the simulated colonic fluid was not changed by intestinal flora with TP2 addition. In conclusion, all of these findings confirmed that TP2, capsular polysaccharides of Bacteroides fragilis , was nonabsorbing and not degraded in gastrointestinal tract, which might alleviate the inflammation by regulating flora or immune mediation in original form.